Analisis Tingkat Kebisingan Lalu Lintas pada Kawasan Kampus 1 Universitas Negeri Gorontalo Ditinjau dari Tingkat Baku Mutu Kebisingan yang Diizinkan - C. Mopili; Y. Kadir; M. Mahmud (REKONSTRUKSI TADULAKO: Civil Engineering Journal on Research and Development, 2023)
An increase in traffic volume causes several negative impacts, one of which is noise. The Campus 1 area of the State University of Gorontalo is one of the education zones where the traffic flow is quite heavy, so a study was conducted to analyze the noise level due to traffic in the area and compare the noise level with the Noise Quality Standard KEP-48/MENLH/11/1996. This research was conducted on roads adjacent to Campus 1 State University of Gorontalo, namely on the roads Jenderal Sudirman (point 1) with road type 2/2 UD, the roads Ir. Hi. Joesoef Dalie (point 2) with road type 4/2 D, and the roads Dewi Sartika (point 3) with road type 2/2 UD. The method used is called "Calculation of Road Traffic Noise (CoRTN). The highest noise level on the road General Sudirman (point 1) is 69,36 dB(A) on Monday, 69,56 dB(A) on Wednesday, and 67,74 dB(A) on Saturday. On Monday, the highest noise level on the roads of Ir. Hi. Joesoef Dalie (point 2) is 72,28 dB(A), on Wednesday, 72,69 dB(A), and on Saturday, 69,90 dB(A). The highest noise level on the road Dewi Sartika is 67,77 dB(A) on Monday, 67,41 dB(A) on Wednesday, and 67,57 dB(A) on Saturday. These results indicate that the noise level in the Campus 1 area of the State University of Gorontalo has exceeded the permitted noise quality standard according to the Decree of the State Minister of the Environment No. 48 of 1996 concerning the noise quality standard for educational areas, which is 55 dB (A).